Precurarization with Rocuronium Prevents Succinylcholine induced Hyperkalemia - Kulsoom Farhat , Akbar Waheed , Anwar Kamal Pasha (Journal of Rawalpindi Medical College, 2012)
Background: To assess the effects of Rocuronium pretreatment on Succinylcholine induced rise in serum potassium. Methods: In this randomized controlled experimental study, sixty adults ASA I or II patients who presented for elective general surgical procedures were included. The patients were divided in two groups of thirty each by a simple randomization. Group "A" received succinylcholine and group "B" received precurarization dose of rocuronium followed by succinylcholine for intubation. Venous blood samples were obtained for estimation of serum potassium (K+) at 0 minutes and after five minutes of intubation. Results: There was a significant rise in serum K+ level from the start of the study to five minutes in group A (p < 0.001). In group B, increase in serum K+ level from start of the study to five minutes was significant (p = 0.001) but it remained within the normal range. The increase in serum K+ level was significantly more in group A as compared to group B (p < 0.001). Conclusion: Pretreatment with rocuronium prevents the rise in serum potassium induced by succinylcholine